MODEL OF PRODUCT DESIGN INTEGRATION WITH THE EFFECT OF SOCIAL NETWORK - Dedi Juliandri Panjaitan; Madyunus Salayan (UIN Sumatera Utara, 2017)
Abstract. The effect of social networking on business marketing strategies becomes inevitable. Taking a step backward, we seek to combine and analyze such effects on new product development and then propose a model for designing product deployment through social networks. We construct a share of choice problem (Kohli and Krishnamurti, 1987), which is a combinatorial optimization problem used generally as one method to analyze conjoint analysis data by marketers to identify products with the largest market share and show how to combine social network effects in a share of choice problem.Keywords: Social Networks, Genetic Algorithm, Marketing.